Shoulder injuries in canoeing and kayaking - Holland, P.; Torrance, E.; Funk, L. (Clinical Journal of Sport Medicine, 2018)
Objective: We report the largest case series of shoulder injuries among paddlers so far to establish common mechanisms and patterns of injury. We also discuss how these injuries were managed and report the proportion of paddlers that return to paddlesport.